Irish Literature Since 1990 Diverse Voices - Brewster, Scott (Manchester University Press, 2011)
This volume explores the meaning of republicanism in contemporary Ireland. While this has often been identified simply with nationalism, the book examines the connections, comparisons and contrasts between Irish republicanism and other strands of republican politics: the ideology and practice of official French republicanism, the broader European and American civic republican tradition and the contemporary revival of this tradition of citizenship.Academics from different disciplines, along with statesmen and politicians from different political perspectives, are brought together to examine the relationship of historical and contemporary Irish republicanism to the wider republican theoretical tradition. The book analyses political positions among those parties describing themselves as republican in Ireland in the twenty-first century and examines the possible relevance of the ideas of the broader republican tradition for future politics in Ireland.